Planificación y ejecución de sesiones de aprendizaje de profesores de inglés en instituciones educativas secundarias públicas y privadas de Iquitos 2023 - Idarraga Fierro, Luis David (2024)
This research was conducted to compare the differences and similarities in the planning and execution of English learning sessions by teachers in public and private secondary educational institutions in Iquitos in 2023. The research design employed was comparative, with mixed-source, contemporary transactional, and multivariable designs. The study included a population and sample of 64 English teachers. A valid and reliable checklist was used as a data collection tool for the review of learning sessions and classroom observation. The results obtained after the research indicate that the mean score for public educational institutions was 11.479, and 12.071 for private educational institutions; on a transformed score to a vigesimal scale, which determines that teachers who work in both types of institutions manage, on average, the planning and execution of learning sessions. Thus, the hypothesis of this research was rejected, as there are no significant differences in the planning and execution of English learning sessions by teachers in public and private secondary educational institutions in Iquitos in 2023. (p-value = 0.539 > α 0.05)